Perbedaan Asupan Karbohidrat Dan Kebiasaan Sarapan Antara Status Gizi Siswa Overweight Dan Non-Overweight Di SMK2 Muhammadiyah Surakarta - Rinanti, Oky Setyaning; , Muwakhidah, SKM., M.Kes; , Endang Nur W, S.St., M.Si.Med (2016)
ABSTRACT OKY SETYANING RINANTI. J 310 141 045 THE DIFFERENCES IN CARBOHYDRATE INTAKE AND BREAKFAST HABIT BETWEEN OVERWEIGHT AND NON-OVERWEIGHT STUDENTS AT MUHAMMADIYAH 2 VOCATIONAL HIGH SCHOOL OF SURAKARTA Background: Results of preliminary survey has been conducted in Muhammadiyah 2 Vocational High School of Surakarta showed that the number of students who were overweight was 18.5 %. Objective: To determine was the differences in carbohydrate intake and breakfast habit between overweight and non-overweight students at Muhammadiyah 2 Vocational High School of Surakarta. Methods: A survey with a case-control design was conducted. The subjects were students of class X and XI, who were overweight (41 respondents) and non-overweight (41 respondents). Carbohydrate intake and breakfast habit data were obtained through 7x24 hour real method. Data were analyzed by Independent T-test and Mann Whitney. Results: Around 61% overweight students had high carboydrate intake. The number of overweight students who did not have breakfast regularly was 63,4%. The different analysis found the carbohydrate intake in both groups showed p value : 0,231, while the breakfast habit in both groups showed p value : 0,000. Conclusion: There was no difference in carbohydrate intake between overweight and non overweight students. There was a difference in breakfast habits between overweight and non overweight students. Suggestion: Future studies may add other variables such as the types of breakfast consumed and carbohydrates (complex or simple) that might affect the nutritional status of overweight and non overweight students. Keywords: carbohydrate intake, breakfast habits, nutritional status overweight and non overweight. References : ( ) 2000-2015